Lemons, or Squeezed for Resources? Information Symmetry and Asymmetric Resources in Biotechnology - Neuberger, Arthur; Oraiopoulos, Nektarios; Drakeman, Donald L. (Frontiers in Pharmacology, 2017)
Thousands of biotech companies are developing promising products, but have insufficient resources to complete the clinical testing process, while large, well-funded companies have increasingly focused on the need to access external innovation. As a result, licensing deals are an essential and growing part of this industry. Yet, casting a shadow over the licensing market is the classic Lemons Problem: Does asymmetrical information put licensees at a severe disadvantage, leading to a market dominated by inferior opportunities, with the best products retained for internal development? Our analysis of clinical stage products developed over three decades shows that there is no Lemons Problem. We discuss the results of this first apples-to-apples analysis of the biomedical licensing market, and suggest reasons why the Lemons Problem does not exist where it might be most expected—in a high technology, knowledge-based industry.